On allowing use of EPF savings as collateral for loans - Mohd Adnan, Normala (The Malaysian Insight, 2023)
Recently, Prime Minister Anwar Ibrahim announced a scheme for targeted withdrawals from the Employees Provident Fund (EPF) for those who experienced post-pandemic financial hardship. This has caused mixed feelings because the government had already allowed several withdrawals from EPF during the Covid-19 pandemic. Most economists expressed their reservations while others felt this initiative could relieve cost of living difficulties.